2013
DOI: 10.5402/2013/159760
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Infection and Dialysis: 2012 Update

Abstract: Hepatitis C virus infection is still common among dialysis patients, but the natural history of HCV in this group is not completely understood. Recent evidence has been accumulated showing that anti-HCV positive serologic status is significantly associated with lower survival in dialysis population; an increased risk of liver and cardiovascular disease-related mortality compared with anti-HCV negative subjects has been found. According to a novel meta-analysis (fourteen studies including 145,608 unique patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 97 publications
(69 reference statements)
3
38
1
Order By: Relevance
“…As seen in Figure-3, our study showed raised AST and ALT levels among three HCV positive haemodialysis patients and ten HCV positive non-haemodialysis patients which is in consensus with other studies such as Fabrizio [24] and Marinaki et al [27] Haemodialysis patients with chronic hepatitis due to HCV infection have serum aminotransferase levels which are at the upper limit but still within the normal range, although higher compared to HCV negative haemodialysis patients. There is no definite explanation regarding the lower transaminase levels observed in haemodialysis patients, although several aetiologies have been postulated-1.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…As seen in Figure-3, our study showed raised AST and ALT levels among three HCV positive haemodialysis patients and ten HCV positive non-haemodialysis patients which is in consensus with other studies such as Fabrizio [24] and Marinaki et al [27] Haemodialysis patients with chronic hepatitis due to HCV infection have serum aminotransferase levels which are at the upper limit but still within the normal range, although higher compared to HCV negative haemodialysis patients. There is no definite explanation regarding the lower transaminase levels observed in haemodialysis patients, although several aetiologies have been postulated-1.…”
Section: Discussionsupporting
confidence: 78%
“…Several studies from India and other countries have reported prevalence rates ranging from 1% to 68%. [23], [24], [25], [26] Health care procedures related to nosocomial infections, unsafe drug injection practices, and blood transfusions are key factors in HCV transmission. In haemodialysis facilities, the most common lapses of healthcare quality are contamination of dialysis systems, inadequate disinfection and cleaning of environmental surfaces, improper contact of health care staff with equipment and patients and mishandling of parenteral medications.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were collected at each study visit before a dialysis, and the plasma HCV-RNA levels were quantified using the Cobas TaqMan version 2.0 assay (Roche Diagnostics, Tokyo, Japan); the lower limits of quantification were 1.2 log 10 IU/mL. The HCV-RNA levels were measured at baseline and at weeks 0, 2,4,8,12,16,20, and 24, as well as at posttreatment weeks 4, 8, 12, and 24. The resistance-associated variants (RAVs) of NS5A-Y93H and L31M/V were identified using direct sequencing [19], which was conducted on all enrolled patients.…”
Section: Clinical Parametersmentioning
confidence: 99%
“…There are six distinguishable HCV genotypes, and the use of conventional interferon (IFN), pegylated IFN-α, or a combination of IFN with ribavirin for treatment depends on the genotype of the HCV virus [2]. Although treatment options for patients on HD are the same as for the general population, it is important to consider that treatment-related toxicity with IFN and ribavirin occurs frequently in patients on HD [3,4]. According to the KDIGO (Kidney Disease Improving Global Outcome) guidelines, monotherapy with standard IFN is the therapy of choice for HCV-infected patients on maintenance HD [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation